2004
DOI: 10.1097/01.aids.0000131301.55204.a7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of HAART advent on admission patterns and survival in HIV-infected patients admitted to an intensive care unit

Abstract: HAART had little impact on ICU utilization by HIV-infected patients. After the introduction of HAART AIDS-related conditions decreased and sepsis increased as reasons for ICU admission. Whereas ICU survival was dependent on usual prognostic markers, long-term survival was clearly dependent on HIV disease stage and HAART availability. In both study periods, at least a half of the HIV infected patients were not on anti-retroviral treatment at the time of ICU admission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
169
6
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(197 citation statements)
references
References 22 publications
18
169
6
4
Order By: Relevance
“…At present, respiratory failure is still the most common indication for ICU admission [9,10], although PCP as a cause of respiratory failure is substantially less common. After the introduction of HAART, the number of hospitalizations related to AIDS decreased, while the incidence of sepsis as a reason for ICU admission increased [11]. Severe sepsis is the major risk factor of hospital mortality in the group of septic patients with HIV/AIDS, significantly affecting short-and long-term mortality.…”
Section: Discussionmentioning
confidence: 99%
“…At present, respiratory failure is still the most common indication for ICU admission [9,10], although PCP as a cause of respiratory failure is substantially less common. After the introduction of HAART, the number of hospitalizations related to AIDS decreased, while the incidence of sepsis as a reason for ICU admission increased [11]. Severe sepsis is the major risk factor of hospital mortality in the group of septic patients with HIV/AIDS, significantly affecting short-and long-term mortality.…”
Section: Discussionmentioning
confidence: 99%
“…The data showed no difference in ICU mortality between those two eras, whereas the long-term survival rate has increased substantially in the ART era [7]. According to van Lelyveld the 1-year mortality decreased from 71% in the pre-HAART era to 50% in the recent period (p = 0.06).…”
Section: Continue Stop or Introduce Art In A Hiv-positive Patient Wimentioning
confidence: 95%
“…With antiretroviral therapy (ART) becoming more popular, sepsis has become a more frequent diagnosis in HIV-positive patients. A prospective study conducted by Casalino et al between 1995 and1999 in Paris showed that after the introduction of ART (in 1997), AIDS-related admissions to the ICU decreased from 57.7% to 37%, and the opposite trend was seen in septic admissions: the percentage of patients with HIV and sepsis admitted to the ICU increased from 16.3% to 22.6% [7]. Even though opportunistic diseases are a decreasing cause of patient hospitalization, respiratory diseases still play a substantial role.…”
Section: Hiv and Sepsismentioning
confidence: 99%
“…Most commonly it is secondary to Pneumocystis jiroveci pneumonia (PCP) and bacterial pneumonia (BP) (Streptococcus pneumoniae, Haemophilus influenzae, Staphylococcus aureus and Pseudomonas aeruginosa), followed by aspergillosis, herpetic infections, oral and pharyngeal candidiasis and cytomegaloviral (CMV) pneumonia, Mycobacterial infections (Mycobacterium tuberculosis and atypical organisms, e.g. M. avium intracellulare) [8][9][10][11]. Other common indications for ICU admission are sepsis and central nervous system (CNS) dysfunction and complications due to Cryptococcal and Candidal meningitis, Subacute encephalitis, Herpes simplex encephalitis, multifocal leukoencephalopathy [10,11].…”
Section: Causes For Icu Admissions Among Hiv Infected Patients In Haamentioning
confidence: 99%
“…M. avium intracellulare) [8][9][10][11]. Other common indications for ICU admission are sepsis and central nervous system (CNS) dysfunction and complications due to Cryptococcal and Candidal meningitis, Subacute encephalitis, Herpes simplex encephalitis, multifocal leukoencephalopathy [10,11]. Lesser common causes are for gastrointestinal (GI) bleeding due to ulceration by infection or Kaposis sarcoma and for cardiovascular disease by opportunistic bacterial infections causing endocarditis and/or congestive cardiac failure.…”
Section: Causes For Icu Admissions Among Hiv Infected Patients In Haamentioning
confidence: 99%